As ações da prefeitura municipal de Campinas frente à demanda por vagas na educação infantil (2001-2008) - Rocha, Ana Cláudia da (2009)
This dissertation presents a study of the formulation and implementation of Schooling Public Policies for children from 0 to 6 years old in the institutions for pre-school education in the city of Campinas, in the interior of São Paulo state from 2001 to 2008. During this period, among other actions, two projects are highlighted which had as their objectives although in one of them this was not explicit the increase in the number of vacancies in local kindergartens and pre-schools and the consequent decrease in the number of children in the waiting lists. The first one implemented from 2001 to 2004, during the petista government of the mayor Antônio da Costa Santos, known as Toninho (murdered in 2001) and after continued by the mayor Izalene Tiene (Campinas vice-mayor who took office after the death of Mayor Antônio da Costa Santos), was called Multi-age Pre-School and based its organization on the grouping of children according to their approximate age. Children used to be divided according to the same age before that. The second project, started in the first pedetista period of government of the mayor Dr. Hélio de Oliveira Santos, from 2005 to 2008, called Naves-Mãe concentrates its attendance in the building of new educational units by the local government and their management by non-governmental institutions through public-private partnerships. These two projects represent two different kinds of public policies that are presented in this dissertation. One of them aimed at enhancing the hole of the local Government in the pre-school education policies as the main responsible actor for the creation, maintenance and vacancies organization in public local institutions for pre-school education and the other which undertook the State s function as the manager of educational policies through public-private partnerships aiming at decreasing the lack of vacancies in preschools in the city of Campinas. This discussion intends to be the base of a search for alternatives of a better and higher attendance in the local children s education.